Adjudication and Treatment of Narcotic Drug Offenders in Ghana - Jacob Agboli (The Journal of Medicine, Law & Public Health, 2023)
Narcotic drug trafficking is a criminal and punishable offence in every country the world over. The use of certain narcotic drugs, on the other hand (especially marijuana), has been legalised in some countries, but under strict regulations. Like other countries, and as a signatory to the United Nations Conventions on narcotic drugs, Ghana has implemented severe punitive sanctions for narcotic drug-related offences to deter people from engaging in this crime. This paper assesses in detail the legal regime dealing with the adjudication and treatment of narcotic drug offenders in Ghana. It reveals that narcotic-related offences carry severe sentences including fines, imprisonment, or both fine and imprisonment. However, as narcotic drug use is currently deemed a public health issue, offenders may be sentenced to treatment facilities rather than imprisonment. Such treatment may be received in either a public or a private facility, and involves a combination of evidence-based and faith-based approaches.